Phytosociology applied to wildlife management - a study on the potentiality for the reintroduction of cervids in the Montemuro-Freita-Arada mountain range - Bellu, Annalisa (2013)
Doutoramento em Engenharia Florestal e dos Recursos Naturais - Instituto Superior de Agronomia